Ecophilosophy as a Way of Life - Mathews, Freya (The Trumpeter, 2023)
The contemporary figure of the ecophilosopher perhaps holds the seeds of something that transcends philosophy in its current strictly academic, professionalized, indeed corporatized mode. This is a "something" that could, on the one hand, tie philosophy back to its own ancient, life-giving, but now lost, root in the Graeco-Roman world, and on the other hand, open it up to people searching outside the academy for a shared and reflective way of life that is authentically Earth-aligned. By means of a detailed comparison of ecophilosophy with the ancient schools of Stoicism and Epicureanism, understood not merely as intellectual discourses but as "ways of life" (Pierre Hadot), I argue that the figure of the ecophilosopher potentially offers to thoughtful people everywhere a radical pathway through the illusions of our current period of decline-and-fall towards a more adaptive life grounded in "direct, unmediated contact with the real."